Effect of Kinesiotaping in Reducing Low Back Pain in Pregnant Women: A Meta-Analysis - Handariati, Atik; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Pregnancy causes physiological changes that affect the musculoskeletal system and usually poses a risk of low back pain. This study aims to analyze the effect of kinesiotaping on reducing low back pain in pregnant women based on the results of a number of previous primary studies.Subjects and Method: This study uses a meta-analysis method with articles searched using the search keywords "Low back pain" OR "pelvic girdle pain" AND "pregnancy" OR "kinesiotaping" OR "kinesio tape" AND "pain reduction" OR "VAS" AND " Randomized Controlled Trial” OR “RCT” from PubMed, google scholar and science direct and processed using RevMan 5.3. The independent variable is kinesiotaping and the dependent variable is low back pain.Results: 9 RCT articles that fit into the inclusion criteria, with a total of 572 samples. Pregnant women with low back pain who received kinesiotaping had an average VAS score of 1.23 units lower than those without kinesiotaping, and the effect was statistically significant (SMD= -1.23; 95% CI -2.30 to -0.16; p= 0.02). In other words, kinesiotaping is effective in reducing low back pain in pregnant women.Conclusion: Kinesio Taping has an effect on reducing low back pain in pregnant women.Keywords: kinesiotaping, low back pain, pregnancy, visual analogue scaleCorrespondence: Atik Handariati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: atikhanda14@gmail.com. Mobile: +6283895940042.Indonesian Journal of Medicine (2022), 07(02): 161-171https://doi.org/10.26911/theijmed.2022.07.02.05